2021
DOI: 10.1002/csr.2136
|View full text |Cite
|
Sign up to set email alerts
|

Board diversity and corporate social performance: Does the family firm status matter?

Abstract: The aim of the study is to investigate whether the board of directors (BoD) diversity affect corporate social performance (CSP), an alternative measure of corporate performance based on social outcomes. The article distinguishes between a structural diversity of boards (proxied by director independence), and a demographic diversity in boards (proxied by gender diversity) and our concept of CSP. The sample is constituted of the firms listed to the FTSE‐MIB index, which comprehends the most Italian capitalized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 133 publications
(315 reference statements)
8
53
1
Order By: Relevance
“…Moreover, Ionascu et al (2018) [30] examine one indicator of the SDGs, which is goal number 5 "Gender Equality", and find that increasing the number of women present on boards has no significant impact on financial performance. This is in line with Veltri et al (2021) [31] who find the same effect of female involvement on board of directors on corporate social performance. This could be the case in well-governed firms; however, adding women to weak corporate governance boards could have a massive improvement on firms' financial performance [1].…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 87%
“…Moreover, Ionascu et al (2018) [30] examine one indicator of the SDGs, which is goal number 5 "Gender Equality", and find that increasing the number of women present on boards has no significant impact on financial performance. This is in line with Veltri et al (2021) [31] who find the same effect of female involvement on board of directors on corporate social performance. This could be the case in well-governed firms; however, adding women to weak corporate governance boards could have a massive improvement on firms' financial performance [1].…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 87%
“…Much of the literature on gender equality has referred to the field of CSR, and has studied the presence of a relationship between gender diversity (especially within the boards of directors) and the adoption of CSR practices, as well as related reporting (Ahmed et al, 2017; Buertey, 2021; Gangi et al, 2021; García‐Sánchez, Amor‐Esteban, & García‐Sánchez, 2021; García‐Sánchez, Gallego‐Álvarez, & Zafra‐Gómez, 2020; Graafland, 2020; Liao et al, 2015; Manita et al, 2018; Post et al, 2011; Rao & Tilt, 2016; Rodriguez‐Gomez et al, 2020; Valls Martínez et al, 2020; Veltri et al, 2021; Vitolla, Raimo, Marrone, & Rubino, 2020; Vitolla, Raimo, & Rubino, 2020). In fact, several studies have highlighted a positive association between women's involvement and CSR performance (Provasi & Harasheh, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In more detail, some authors have highlighted that gender diversity provides the top management with a better understanding of the complexities of the organizational environment and thus improves decision making (De Luis‐Carnicer et al, 2008; Dwyer et al, 2003; Luanglath et al, 2019). As well as financial performance, gender diversity in the top management positively influences the social performance of firms (Campbell & Mínguez‐Vera, 2008; Hafsi & Turgut, 2013; Veltri et al, 2021; Yasser et al, 2017). Prior studies have demonstrated that women in top management positions show a greater concern for social relationships, risk awareness, and stakeholder engagement (Amorelli & García‐Sánchez, 2020).…”
Section: Introductionmentioning
confidence: 99%